Construction of a Ge-BGO Compton Suppression Gamma-ray Spectrometer and Its Application to Environmental Samples. Part 1: The System of the Spectrometer and Its Basic Performance - Takao Tojo; Muhammad Zainuddin; Widodo Soemadi (Widyanuklida, 1999)
ABSTRACT In order to develop a very high sensitive Ge gamma-ray spectrometer, a Compton suppression gamma-ray spectrometer with a BGO guard detector system has been constructed. The BGO detector system detects 88% of the gamma-rays from 60Co that are committing to the principle of the suppression system. Peak-to-Compton ratio for the 661 keV gamma-rays from 137Cs has been improved from 128 to 786 with the Compton suppression spectroscopy. By the development of the spectrometer the minimum acceptable radioactivity of 137Cs has been improved from 0.091 Bq to 0.044 Bq with the coeficient of variation of 30% and measurement time of 8 hours. ABSTRAK Untuk mengembangkan spektrometer sinar-X Ge dengan kepekaan yang sangat tinggi, telah dibuat sebuah sistem spektrometer sinar-X penindas Compton dengan menggunakan detektor pelindung BGO. Sistem detektor BGO mendeteksi 88%. sinar gamma dari 60Co yang digunakan dalam prinsip sistem penindas. Peak-to-Compton ratio untuk sinar gamma berenergi 661 keV dari 137CS telah diperbaiki dari 128 menjadi 786 dengan spektroskopi penindas Compton. Melalui pengembangan spektrometer ini radioaktivitas 137Cs minimum yang dapat diterima meningkat dari 0.091 Bq menjadi 0.044 Bq dengan koefisien variasi 30%. dan waktu pengukuran 8 jam.